Mediation in Class Actions: Poland and Lithuania - Bartkus, Jurgis; Skibińska, Magdalena (Teisė, 2026)
This paper analyzes mediation and its possibilities in class actions in two jurisdictions: Poland and Lithuania. The aim of this paper is to evaluate and compare the current Polish and Lithuanian legal frameworks in order to assess whether the existing regulations facilitate the resolution of class actions through mediation. In this paper, we conclude that, in Poland, mediation in class actions is regulated more comprehensively, however, at the same time, the Lithuanian civil procedure – at least at a first glance – offers broader potential opportunities for the amicable resolution of class actions than the Polish civil procedure.